Viability of Brazilwood seeds (Caesalpinia echinata Lam.) stored at room temperature in controlled atmospheres - Martini Neto,Nestor (2015)
Seed storage at room temperature is an important and low-cost tool for ex situ conservation. However, the high rates of seed deterioration could reduce the potential for storage in this condition. Therefore, the knowledge of the suitable water content for this type of storage plays a critical role. This study aimed to assess the time required to stabilize the relative humidity (RH) in sealed flasks with saturated salt solutions, with or without the introduction of seeds of Caesalpinia echinata, as well as to assess the viability of these seeds stored in environments with different hygroscopic equilibrium. The results showed that 2 and about 12 days are needed to stabilize the RH, respectively, without or with the seeds. The amount of saturated salt solutions in this airtight environment influences both the speed to equilibrate the RH and the final values of the RH. Seeds of Caesalpinia echinata tolerate drying up to 5% water content (wet basis); however, the viability of these seeds at room temperature is maintained for short periods even at low water content.